Investigation of Antibacterial Activity of Carvacrol, Alpha-Terpineol and Eugenol on Extended-Spectrum Beta-Lactamase-Producing Escherichia Coli Strains Isolated from Chicken Meat - Tülin Güven Gökmen (Turkish Journal of Agriculture: Food Science and Technology, 2025)
Extended-Spectrum Beta-Lactamase-producing Escherichia coli, previously isolated only from clinical samples, is now also isolated from foods. This poses a major threat to public health and food safety. Food contamination is currently prevented with various chemical substances. However, due to their harmful effects, the usability of food-grade natural antimicrobials is being investigated. In this study, the antibacterial effects of Carvacrol, Alpha-Terpineol and Eugenol on Extended-Spectrum Beta-Lactamase-producing Escherichia coli isolates isolated from chicken meat were examinated. Broth dilution and Well-Diffusion methods were used. As a result of broth dilution test of carvacrol, minimum inhibitory concentration and minimum bactericidal concentration values were determined as 0.78µL/mL. Minimum Inhibitory Concentration value was determined as 3.125-6.25 µL/mL; Minimum Bactericidal Concentration value was 3.125-12.5 µL/mL for Alpha-Terpineol. For Eugenol, Minimum Inhibitory Concentration value was 3.125-6.25 µL/mL, Minimum Bactericidal Concentration value was 6.25-12.5 µL/mL. When the Well-Diffusion test inhibition zones were examined, it was measured as 35-38 mm for Carvacrol, 18-23 mm for Alpha-Terpineol, and 22-30 mm for Eugenol. It was found that Carvacrol was the most effective, followed by Eugenol. In conclusion, the use of Carvacrol, Alpha-Terpineol and Eugenol products can be recommended in various applications to prevent the spread of Extended-Spectrum Beta-Lactamase-producing Escherichia coli isolates in the food chain.